A gyermekjogok szabályozása és e jogok érvényesülése a szülők „válása” esetén - Visontai-Szabó, Katalin (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
Ellen Key was right when, in 1902, she predicted that the 20th century would be the century of the children. From the brief historical description of my study, it can be seen, that the treatment of children changed a lot in the 1900s, they turned from little adults owned by their parents to individuals with independent rights, who deserve protection. The rights of children are guaranteed by many national and international documents, which I tried to collect. The greatest burden for children is the dissolution of the parent’s relationship, so it is particularly important in this process that the parents and the authorities take into account the children’s rights, focus on the child’s best interests in their decisions and protect them from physical and mental harm.